2003
DOI: 10.1063/1.1556963
|View full text |Cite
|
Sign up to set email alerts
|

Anomalous power and spectrum dependence of terahertz radiation from femtosecond-laser-irradiated indium arsenide in high magnetic fields up to 14 T

Abstract: We report on the terahertz radiation from femtosecond-laser-irradiated indium arsenide in high magnetic fields up to 14 T. It is found that the radiation power exhibits anomalous magnetic-field dependence, including saturation, decrease, and recovery up to 14 T. Moreover, the radiation spectrum possesses a clear periodic structure over 6 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…At the same time, the exponent has been varied within fairly wide limits. This fact agrees with the results of [2], where the quadratic dependence of power corresponding to the terahertz pulse from InAs on the magnetic induction was observed under irradiation of the crystal surface with femtosecond laser pulses. The theoretical calculations of the radiation power are in satisfactory agreement with the experimental results presented in [4].…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…At the same time, the exponent has been varied within fairly wide limits. This fact agrees with the results of [2], where the quadratic dependence of power corresponding to the terahertz pulse from InAs on the magnetic induction was observed under irradiation of the crystal surface with femtosecond laser pulses. The theoretical calculations of the radiation power are in satisfactory agreement with the experimental results presented in [4].…”
Section: Resultssupporting
confidence: 82%
“…In particular, the radiation of semiconductors in crossed electric and magnetic fields and generation of terahertz pulses with picosecond duration under irradiation of the semiconductor surface in magnetic field by femtosecond laser pulses were analyzed [1][2][3].…”
Section: Introductionmentioning
confidence: 99%
“…As the magnetic field increases further, THz-radiation power recovers up to 5 T. We also observed a similar magnetic-field dependence for InAs. 13 Saturation and recovery in InSb occurred in a much lower magnetic field, as expected from the smaller effective mass of carriers in InSb compared to that of InAs. At 780 nm optical excitation, the magnetic-field dependence was very similar to that of the 1560 nm optical excitation case, except that its power is lower by an order of magnitude.…”
Section: Significant Enhancement Of Terahertz Radiation From Insb By mentioning
confidence: 88%
“…12 Furthermore, we have observed anomalous magnetic-field dependence of THz-radiation power, including saturation, decrease, and recovery. 13 The saturation point found at around 3 T could lead to a practical compact THz-radiation source with a specially designed compact magnet. 14 For the enhancement of THz-radiation power, a smaller effective mass of photoexcited carriers is considered to be advantageous.…”
Section: Significant Enhancement Of Terahertz Radiation From Insb By mentioning
confidence: 99%
“…McLaughlin et al [145] reported a quadratic dependence of the THz emission on magnetic field up to 3 T. Beyond 3 T, Ohtake et al [146] demonstrated that the radiated THz power saturates at 4 T, decreases to a minimum at 6 T, and increases again at 14 T.…”
Section: Inas and Other Narrow-gap Semiconductorsmentioning
confidence: 99%